The Night-Time Environment in French Mountain Areas. A Resource and a Transition Operator Towards Sustainability - Samuel Challéat; Dany Lapostolle; Johan Milian (Revue de Géographie Alpine)
This article presents our approach to construct the night-time environment (NE) as an interdisciplinary research subject. Understood within the framework of various French mountain areas, we show that the NE is highly indicative of different development trajectories. We analyse them by combining traditional social science research into territory with the ecosystem approaches of the experimental sciences. We show how the NE resource (NER) is transformed into an operator that facilitates the transition towards sustainability. By highlighting three of the NE’s specifications, this work lays the groundwork for a transdisciplinary approach.